Drug Utilization Review of Antibiotics in Geriatric Outpatients at Cilacap Regional General Hospital During the COVID-19 Pandemic - Cindy Ade Safitri; Khamdiyah Indah Kurniasih; Fauziah Fauziah; Fiqih Nurkholis; Ikhwan Yuda Kusuma (JURNAL ILMIAH FARMASI SIMPLISIA, 2025)
Infectious diseases are challenging for the geriatric due to higher infection risk and atypical symptoms, leading to more diagnostic uncertainty. This study aimed to evaluate antibiotic use patterns among geriatric outpatients at Cilacap Regional General Hospital in Indonesia during the COVID-19 pandemic. A retrospective study analyzed electronic medical records of geriatric outpatients who received antibiotics from January to December 2021. Data collected included demographic characteristics, types of antibiotics based on the AWaRe classification, route of administration, ICD-10 codes, and antibiotic use. The results showed that the age group of 65–69 years was the most frequent user of antibiotics, with solid oral formulations being the most commonly prescribed. Most antibiotics prescribed belonged to the Watch category, such as cefixime and levofloxacin. The most common diagnosis based on ICD-10 codes was Z098. These findings indicate a tendency toward the use of broad-spectrum antibiotics, which poses a risk of increasing antibiotic resistance. Therefore, stricter antibiotic stewardship interventions and continuous education are necessary to improve the rational use of antibiotics in the geriatric population.